(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The rapid expansion of distributed computer networks, cloud computing environments, Internet of Things (IoT) systems, and decentralized applications has significantly increased the demand for secure authentication and access control mechanisms. Traditional centralized authentication systems rely on trusted third-party servers that often-become performance bottlenecks and single points of failure. Furthermore, centralized identity management infrastructures remain vulnerable to insider attacks, credential theft, unauthorized privilege escalation, distributed denial-of-service attacks, and database compromise. As distributed computing environments continue to grow in complexity, there is an increasing need for decentralized security architectures capable of providing secure, transparent, and tamper-resistant authentication and authorization services. Between 2008 and 2015, extensive research focused on authentication protocols, role-based access control (RBAC), attribute-based access control (ABAC), capability-based security models, public key infrastructure (PKI), identity management systems, and cryptographic authentication techniques for distributed computer networks. These studies established the theoretical foundations for secure identity verification and authorization. Following the emergence of blockchain technology and smart contracts between 2016 and 2018, researchers began exploring decentralized authentication frameworks that eliminated reliance on centralized authorities while improving transparency, trust, auditability, and resilience against security attacks.